Courses for change in writing (Boynton/Cook Publishers, Inc., 1984)
Contents: Introduction: on the design of writing courses; Language and reality: an island perspective; Writing and regional experience: a view from the Delta; Play and work: creativity in expository writing; Winners and losers: a course for basic writers...